2006
DOI: 10.1021/jo061385s
|View full text |Cite
|
Sign up to set email alerts
|

Expanding the C2-Symmetric Bicyclo[2.2.1]hepta-2,5-diene Ligand Family:  Concise Synthesis and Catalytic Activity in Rhodium-Catalyzed Asymmetric Addition

Abstract: New C2-symmetric bicyclo[2.2.1]hepta-2,5-dienes bearing methyl and phenyl substituents at the 2 and 5 positions were prepared enantiomerically pure through a two-step sequence starting from the readily available bicyclo[2.2.1]hepta-2,5-dione. Due to the instability or volatility of these dienes, their isolation was achieved through the formation of the corresponding stable [RhCl(diene)]2 complexes. These chiral rhodium complexes displayed high activity and enantioselectivity (up to 99% ee) in the rhodium-catal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
57
0
1

Year Published

2007
2007
2014
2014

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 96 publications
(60 citation statements)
references
References 36 publications
2
57
0
1
Order By: Relevance
“…The following Negishi coupling [15] was performed with FeA C H T U N G T R E N N U N G (acac) 3 as the catalyst under the cross-coupling conditions recently described by Hayashi. [13] In this manner, the chiral 3,6-dibenzylated bicyclo-A C H T U N G T R E N N U N G [3.3.0]octadiene ligands (3aR,6aR)-and (3aS,6aS)-10b were accessible in 75 % and 76 % yield, respectively. This synthesis route allows a variation of the substituent, yielding, for example, also ligand (3aS,6aS)-10a in 62 % (see Experimental Section).…”
Section: Ligand Synthesismentioning
confidence: 99%
See 1 more Smart Citation
“…The following Negishi coupling [15] was performed with FeA C H T U N G T R E N N U N G (acac) 3 as the catalyst under the cross-coupling conditions recently described by Hayashi. [13] In this manner, the chiral 3,6-dibenzylated bicyclo-A C H T U N G T R E N N U N G [3.3.0]octadiene ligands (3aR,6aR)-and (3aS,6aS)-10b were accessible in 75 % and 76 % yield, respectively. This synthesis route allows a variation of the substituent, yielding, for example, also ligand (3aS,6aS)-10a in 62 % (see Experimental Section).…”
Section: Ligand Synthesismentioning
confidence: 99%
“…After dehydration with POCl 3 in pyridine at 80 8C, [1f] ligands (3aR,6aR)-and (3aS,6aS)-10a were isolated in 50 % and 62 % yield. Deprotonation of diones (3aR,6aR)-and (3aS,6aS)-7 with KHMDS [13] and subsequent treatment with N-(2-pyridyl)triflimide [14] (2-PyNTf 2 ) in THF at À78 8C gave the bistriflates (3aR,6aR)-and (3aS,6aS)-9 in 56-58 % yield. The following Negishi coupling [15] was performed with FeA C H T U N G T R E N N U N G (acac) 3 as the catalyst under the cross-coupling conditions recently described by Hayashi.…”
Section: Ligand Synthesismentioning
confidence: 99%
“…Since the first application of chiral (S,S)-2,5-dibenzylbicyclo[2.2.1]heptadiene ((S,S)-L27b) in the addition of phenylboronic acid to cyclohex-2-enone by Hayashi and coworkers [93], a variety of bicyclic diene scaffolds [94][95][96][97][98][99][100][101][102][103][104] has been successfully applied (Scheme 1.15). Independently, Carriera and coworkers reported the application of a chiral diene for Ir-catalyzed allylic substitution [105].…”
Section: Diene Ligandsmentioning
confidence: 99%
“…These independent discoveries have spurred intense research efforts in homogeneous catalysis which were compiled in 2008 in an excellent review by Carreira and Grützmacher [106]. An examination of the substituent-effect in chiral bicyclo[2 : 2 : 1]heptadiene scaffold revealed that just two methyl groups in ligand L27a are sufficient to impart a high enantioselectivity (95% ee) in the ECA reaction [99]. Moreover, variation of the alkyl group to Bn (L27b), Cy (L27d), allyl (L27f ), and i-Bu (L27e) does not significantly influence the selectivity when compared to L27a [107]; only when moving to a phenyl substituent is a higher ee-value obtained.…”
Section: Diene Ligandsmentioning
confidence: 99%
“…[8] On the metal side, the fragments include {Rh(nbd)} + (nbd = bicyclo[2. . [9] Reaction of a corannulene and a [{(nbd)RhCl} 2 ] derivative activated by silver(I) in dichloromethane at room temperature produces the expected complexes 6-9 (Scheme 1).…”
mentioning
confidence: 99%